Perancangan dan Analisis Jaringan FTTB Berbasis Teknologi GPON Pada Bangunan Hotel - Oktavianus, Yoppi Lisyadi; Elfitri, Ikhwana; Purbo, Onno Widodo (Jurnal Inovtek Polbeng Seri Informatika, 2023)
This paper presents the design and implementation of a Fiber To The Building (FTTB) network infrastructure based on Gigabit Passive Optical Network (GPON) technology in a hotel cluster building located in West Sumatra, Indonesia. GPON technology was selected for its cost-effectiveness and efficiency in the distribution area, particularly when the terminal bandwidth is set atÂ â‰¤500 Mbps. The waterfall method was utilized in the network's design. The results were tested and analyzed across three Open System Interconnection (OSI) layers: the physical layer, represented by the link power budget; the datalink layer, represented by the Traffic Container (T-CONT); and the network layer, represented by the QoS network performance. The link power budget showed a minimum received power of -16.41 dBm on the downlink and -18.95 dBm on the uplink, with a power margin value above zero. T-CONT has been implemented with the fixed bandwidth value set to provide a bandwidth guarantee meeting the minimum requirement of 1.1 Mbps. The network performance of the FTTB GPON demonstrated excellent performance, as per Internet Protocol Harmonization Over Network (TIPHON) standards, recording a latency of 1.18 ms, jitter of 0.18 ms, and zero packet loss